PENGARUH STATUS SOSIAL EKONOMI ORANG TUA TERHADAP MOTIVASI BELAJAR MAHASISWA PROGRAM STUDI PEDIDIKAN PANCASILA DAN KEWARGANEGARAAN FKIP UNIVERSITAS RIAU - Josepta, Indra; Arianto, Jumili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research of background overshadow by motivation learn seen student of social status phenomenon of old fellow economics which compose work, production and education of old fellow. This Formula research internal issue is